Solar Thermal Energy Utilization: Design Innovations and Performance Enhancement Techniques - Prashant Roy (International Journal of Energy and Thermal Applications, 2025)
The utilization of solar thermal energy has become increasingly significant in the pursuit of sustainable and low-carbon energy solutions. Unlike photovoltaic technologies that directly convert sunlight into electricity, solar thermal systems focus on harnessing solar radiation to generate heat, which can then be applied to diverse sectors such as water heating, space conditioning, industrial process heating, and power generation. In recent years, substantial research efforts have been directed toward enhancing the efficiency, reliability, and economic feasibility of these systems through design innovations and performance improvement strategies. This review provides an in-depth overview of the latest advancements in solar thermal technology, highlighting the interplay between collector designs, thermal energy storage techniques, and system optimization methods.Particular attention is given to the evolution of collector technologies ranging from traditional flat plate and evacuated tube collectors to advanced concentrated solar power systems that employ parabolic troughs, heliostats, and Fresnel lenses. The incorporation of novel materials such as selective absorber coatings, nanofluids, and phase-change materials (PCMs) has significantly improved energy capture and retention. Furthermore, innovations in thermal energy storage—including sensible, latent, and thermochemical methods—have enhanced system flexibility and reliability, enabling better integration of solar thermal energy into industrial and grid-based applications. Hybrid configurations, such as photovoltaic-thermal (PV/T) systems, along with intelligent tracking and control mechanisms, have further contributed to overall system optimization.Despite these advances, challenges related to high installation costs, intermittency of solar radiation, and long-term material stability remain. The article concludes by outlining future research directions, including the use of cost-effective nanomaterials, recyclable storage media, and artificial intelligence-based predictive control systems. By consolidating design innovations and performance enhancement techniques, solar thermal energy can play a crucial role in addressing global energy demands while contributing to climate change mitigation and energy security.
Keywords: High efficiency in heat production; energy landscape; photovoltaic technologies; power generation; solar thermal energy